Essays on political influence and sustainability in banking and financial markets - Wenjing, Zhang (2025)
This thesis investigates the effects of environmental events and public governance within the Chinese context, focusing on three key research questions: (1) Do local firms strategically enhance Corporate Social Responsibility (CSR) following regional pollution emergencies? (2) How does the 'policy mix' of green credit policies and government subsidies influence high-quality environmental innovation in high-polluting firms? (3) What is the impact of political corruption on stock liquidity? Utilizing a large sample of Chinese listed firms, this thesis employs robust empirical methods, including instrumental variables, propensity score matching (PSM), and difference-in-difference tests, to ensure the validity of its findings. The research reveals that firm-level outcomes are significantly influenced by regional pollution emergencies, environmental policy mixes, and political corruption. Chapter 1 addresses the rising incidence of pollution emergencies in China and examines how local firms use CSR initiatives to build trust and counteract negative stakeholder sentiments following severe pollution events. It identifies political dependency, institutional ownership, and public monitoring as primary drivers of enhanced CSR activities, contributing to the literature on corporate responses to environmental shocks. Chapter 2 explores the impact of the Green Credit Guidelines (GCGs) in China and the moderating role of government subsidies. The findings indicate that GCGs negatively affect high-quality environmental innovation among high-polluting firms, but government subsidies can mitigate this negative impact. This work adds to the literature on the implications of environmental policy mixes. Chapter 3 investigates the relationship between political corruption and stock liquidity, revealing that local political corruption negatively impacts stock liquidity through informational channels and investor trading activities. This chapter contributes to the extensive research on the effects of corruption. By focusing on environmental innovation, CSR, and stock liquidity, this thesis highlights significant contributions to the broader literature on political influence and sustainability in banking and financial Markets.